Perlindungan Hukum Terhadap Korban Konflik Sosial - Petrus Soerjowinoto (JURNAL HUKUM, POLITIK DAN KEKUASAAN, 2020)
The fact shows that social conflicts remain frequently happening in Indonesia until today. The social conflicts manifest in various forms and happen in different sites and are caused by various reasons.The motto of Bhinneka Tunggal Ikarepresenting Indonesia as a nation having diversity in tribes, religions, races, and groups is indeed to be a significant factor and capital that contributes to the establishment of a unitary state of the Republic of Indonesia. However, the motto, on the other hand, can also be a seed of the emergence of vertical and horizontal conflicts. It could be noted that there were a lot of serious social conflicts that caused casualties in the forms of death, loss of property, social and  environmental damages, human rights violations and so on. As a critical reflection, Indonesian nation is now being faced to challenges that tend to lead to disintegrative and threatening situations that will probably threaten the existence of the nation. Besides, there are a number of sites having potential social conflictsand they spread throughout Indonesia. This needs to be overcome.